Brewing Loyalty in the Coffee Shop Industry: The Role of Brand Experience and Service Quality in Shaping Customer Commitment - Wei Chien Ng; Yu Xiong; Jingxuan Xiong; Zetian Xin; Shuhan Xie; Yashasvi Srivastava; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
This study investigates the determinants of customer loyalty toward The Coffee Bean Tea Leaf (CBTL) in Malaysia by analysing the influence of service quality, ambience/environment, and staff behaviour, with customer satisfaction as a mediating factor. Using a quantitative approach, data were collected from 360 respondents through an online survey, with most participants being female and aged between 21 and 30 years. All constructs demonstrated acceptable reliability, with Cronbach’s alpha values above 0.70, and respondents generally reported positive perceptions of the assessed variables. The findings reveal strong positive correlations among all constructs, and regression analysis shows that service quality (? = 0.287, p .001), ambience/environment (? = 0.305, p .001), and staff behaviour (? = 0.305, p .001) significantly predict customer satisfaction, explaining 69.1% of its variance (R² = 0.691). Customer satisfaction also exhibits a strong positive effect on customer loyalty (? = 0.829, p .001), accounting for 68.8% of the variance (R² = 0.688). Overall, the study confirms that customer satisfaction plays a crucial mediating role linking service-related factors to loyalty outcomes and provides practical insights for café managers seeking to strengthen customer retention in Malaysia’s competitive coffee industry